Neferine prevents NF‐κB translocation and protects muscle cells from oxidative stress and apoptosis induced by hypoxia. (4th April 2016) - Baskaran, Rathinasamy; Poornima, Paramasivan; Huang, Chih Yang; Padma, Viswanadha Vijaya
Abstract: Neferine (Nef), a bisbenzylisoquinoline alkaloid from lotus seed embryo has a wide range of pharmacological activities. Possible molecular mechanism for the cytoprotective action of Nef during hypoxic stress has not been explored till now. Hence, this is an attempt to elucidate the molecular mechanism involved in the Nef mediated cytoprotection on hypoxia‐induced cell injury. Cytoprotective dose of Nef in muscle cells (Human rhabdomyosarcoma cells) exposed to hypoxia was determined by MTT assay. Nef at 500 nM offered better cytoprotection and was used for all the experiments. ROS, intracellular calcium accumulation and mitochondrial membrane (Δ ψM ) potential were measured using fluorescent probes. Further, we evaluated the effect Nef on hypoxia induced inflammatory and apoptotic responses by FACS and analyzing the expression patterns of NF‐κB, COX‐2, HIF‐1α, caspase‐3, caspase‐9, Bcl2, and Bax. The results of this study revealed that pretreatment of the cells with Nef significantly decreased the Δ ψM and ROS in the cells subjected to hypoxia. Further, Nef inhibited NF‐κB there by inhibiting the expression of its downstream regulator COX‐2, while it induced the functional HIF‐1α expression. The results also indicate that Nef significantly inhibited the ROS dependent mitochondrial mediated apoptosis induced during hypoxia. The cytoprotection elicited by Nef in a model of hypoxia induced cell death involves both anti‐inflammatory and anti‐apoptotic response. These results suggest that Nef may be used as prophylactic agent against the hypoxic challenge. © 2016 BioFactors, 42(4):407–417, 2016